Transport properties of the transverse charge-density-wave system Fe3O2BO3 - Fernandes, J. C.; Guimaraes, R. B.; Continentino, M. A.; Ziemath, E. C.; Walmsley, L.; Monteverde, M.; Nunez-Regueiro, M.; Tholence, J. L.; Dumas, J. (American Physical Soc, 2005)
We study the transport properties of the charge-density-wave system Fe3O2BO3. ac conductivity measurements for different frequencies are presented for temperatures above and below the structural transition. dc conductivity, as a function of temperature and pressure, yields the variation of the transition temperature with external pressure. Below this transition the conductivity is thermally activated in a wide range of temperature and the gap obtained is strongly pressure dependent. The ac conductivity at sufficiently low temperatures below the transition is ascribed to the excitation of local defects associated with domain walls and which are characteristic of the one-dimensional nature of the Fe3O2BO3 system.